Voluntary pharmacological drug poisoning in 267 adolescents - Lage, Joana; Paixão, Filipa; Faria, Teresa; Almeida, Helena Isabel (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Adolescence, a period of biopsychosocial change, is particularly vulnerable to unsafe behaviors such as voluntary drug poisoning (VDP). The main objective of this study was to characterize the epidemiology, clinical characteristics and management of admissions due to VDP in a Pediatric Emergency Department in Lisbon. Methods: Retrospective study between january 2015 and december 2022 by reviewing computerized inpatient records of all admissions of children up to 18 years old due to VDP. Results: During the study period, a total of 267 admissions were identified, with a predominance of female gender and a median age of 16 years. Regarding personal history, 83.1% of adolescents had a psychiatric disorder, and 74.8% of these individuals were receiving medication. Approximately 39% had experienced at least one previous episode of VDP. Half of the patients were symptomatic upon admission, with neurological manifestations being the most common. Among the medications involved, acetaminophen was the most frequently identified (23.6%), and within the pharmacological classes, antipsychotics were the most commonly used, followed by benzodiazepines and antidepressants. Interventions in the Emergency Department included activated charcoal, gastric lavage and specific antidotes targeted at the ingested toxin. The primary precipitating factors were family conflicts, conflicts with a partner and bullying. Conclusions: There is a significant association between VDP and psychiatric disorders. The high prevalence of medication use among these patients emphasizes the need for close monitoring of those undergoing pharmacological treatment. The identified triggering circumstances underscore the critical role of psychosocial factors, highlighting the importance of targeted interventions.